IMPACT OF COVID-19 ON SPINE SURGERIES IN A HIGH COMPLEXITY EMERGENCY HOSPITAL - MATEUS BERGAMO LOMAZ; MURILO RIBEIRO SANCHES; JULIANE LEITE ORCINO; GUILHERME DE MATOS ABE; MATHEUS PEREIRA SANTANA; MURILO TAVARES DAHER (Coluna/Columna, 2024)
ABSTRACT Objective: To study the impact of the COVID-19 pandemic on spine surgeries at a Reference Center for High Complexity Urgencies in Goiás. Methods: A retrospective, observational study was carried out based on data from medical records of patients undergoing spine surgery between September 2017 and September 2021. Volunteers were divided into two groups: before and during the pandemic, considering April 2020 as a starting point. The following was extracted from the medical records: age, gender, education, etiology, neurological deficit, region of the spine addressed, mechanism of trauma, fractured vertebrae, type of fracture, length of stay in the ICU, COVID test (PCR), and deaths. Student t, chi-square, and Fisher’s exact statistical tests were used to compare the preand post-pandemic profiles. In addition, Spearman’s correlation test was applied to verify the correlation between variables, considering p<0.05. Results: 388 medical records were analyzed, showing a 15% increase in spine surgeries during the pandemic. There was a significant difference in the etiology of surgeries (p=0.05), with lumbar trauma being more prevalent in men and also more cases of neurological deficits (p=0.001). There was also a reduction in the length of stay in the ICU (p=0.0001), which was lower during the pandemic. Conclusion: The COVID-19 pandemic did not directly impact the number of surgeries performed at a Reference Hospital in High Complexity Urgencies in Goiás, but there was a prioritization of emergency surgeries. Level of Evidence II; Retrospective Study.